Influence of processing and preservation process on technological and organoleptic qualities of Coptodon guineensis and Sarotherodon melanotheron in south Bénin. - ASSOGBA, Martinien Hospice Mahussi; SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; AHOUNOU, GBÊNAGNON SERGE; DAHOUDA, Mahamadou; CHIKOU, ANTOINE; Farougou, Souaïbou; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2018)
Fish is one of the most important protein sources in Benin. Inappropriate processing and preservation processes could deteriorate fish quality traits. The study aims to evaluate the effect of processing and preservation processes on the technological and organoleptic qualities of fish in south Benin. Thus, 86 fish processors and wholesalers were surveyed. In total 120 samples of S. melanotheron and C. guineensis were randomly collected for the technological and organoleptic quality evaluation. Technological mesures (yields, pH, and water content) and sensory tests (texture, color, and freshness state) were performed to evaluate fillet quality. The frying was performed through the following stages: oil heating, flour mixture with fish and putting the mixed fish with flour in oil. The smoking is performed through the following stages: soft fires and fire with smoke. S. melanotheron presented higher (P<0.05) eviscerated weight (113.33g) than C. guineensis (85.34g). C. guineensis presented higher (P<0.05) fillet yield and pH (6h, 24h and 48h) than S. melanotheron. As for the organoleptic quality, the yellow index, lightness and chroma were higher (P<0.001) in S. melanotheron than in C. guineensis. The lightness of fried and smoked S. melanotheron was higher (P<0.05) than that of fried and smoked C. guineensis. The texture was similar between the treatments (P>0.05). The tenderness, juiciness, flavor and the consumer global acceptance mark were not different between the fish and between the cooking modes. The optimization of fish processing and preservation processes will guarantee a better technological and organoleptic quality of fish to the consumer.
Keywords: Fish; Smoking; Frying; Fillets; Abomey-Calavi.